FRI0261 Observational Study of Outcome in Patients with Early Diffuse Cutaneous Systemic Sclerosis Treated with Immunosuppressive Therapies (ESOS Study). (15th July 2016) - Herrick, A.L.; Pan, X.; Peytrignet, S.; Hesselstrand, R.; Mouthon, L.; Brown, E.; Czirjak, L.; Distler, J.; Distler, O.; Fligelstone, K.; Gregory, W.; Ochiel, R.; et al.
Abstract : Background: Early diffuse cutaneous systemic sclerosis (dcSSc) has high morbidity and mortality, and there is currently no cure. Objectives: The main objective of ESOS (European Scleroderma Observational Study) was to compare the effectiveness of currently used immunosuppressant treatments. Methods: ESOS was a prospective observational cohort study, capturing entry and outcome data in a standard way. Four recommended treatment protocols were decided by the steering committee: methotrexate (MTX), mycophenolate mofetil (MMF), cyclophosphamide, and "no immunosuppressant". Patients were assessed at baseline, and then 3-monthly for 24 months or (for those entering the study subsequent to September 2013) at least 12 months. The primary outcome measure was the change in modified Rodnan skin score (mRSS – 17 sites) between 0 (baseline) and 12 months. Secondary endpoints largely reflected routine clinical practice and are not reported here. Effects of treatment on the skin score were assessed using linear regression with baseline treatments as predictors. Confounding by indication at baseline was accounted for using inverse probability of treatment (IPT) weights, while censoring weights adjust for bias due to patient attrition. Survival in each protocol was estimated using Kaplan-Meier curves and survival differences were tested based on the results of an IPT-weighted Cox regression model. Results: Target recruitment was achieved, with 326 patients from 50 centres (median age 52.3 years, 72% female, median disease duration 11.1 months). Because this was not a randomized study, the number of patients starting on each treatment protocol differed: 65 MTX, 117 MMF, 87 cyclophosphamide, and 57 no immunosuppressant treatment. 273 patients (84%) completed 12 months follow-up and 179 (55%) 24 months follow-up. Median mRSS at baseline was 21.0 units. After 12 and 24 months, 153 (56%) and 139 (78%) of remaining patients had an improved skin score with respect to baseline. The mean change in mRSS after 12 and 24 months was -2.9 and -6.8 units. Predicted decreases in mRSS in each of the protocols are summarized in Figure 1 . In both weighted and unadjusted models, the differences between the treatment groups are non-significant (p=0.27 and p=0.16). At 24 months, Kaplan-Meier predicted survival rates (adjusted for confounding) are 94% (MTX), 90% (MMF), 91% (cyclophosphamide) and 87% (no immunosuppressant). However, differences are non-significant (p=0.42). Conclusions: 1. All groups showed improvement in MRSS which was not significantly different between groups although there was a trend in favour of methotrexate and MMF. 2. Survival was similar between groups although the no immunosuppressant group had lower survival (but it is important to stress that this was not a true "control" group). Disclosure of Interest: None declared